Strategi Pembelajaran Mandiri - Sultang, Muhammad Nor Kholis; U, M. Shabir; U, Usman (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines independent learning strategies. This study uses a qualitative approach with the main data source from library data. The data is analyzed qualitatively. Independent learning is a learning strategy that aims to build individual initiative, independence, and self-improvement. The focus is on independent learning planning by students with the help of educators. Independent learning can also be done with friends or as part of a small group. The characteristics of independent learning are: pyramid-shaped goals, learning sources and media, place of learning, learning time, tempo and rhythm of learning, learning methods, and evaluation of learning outcomes. To implement independent learning strategies, methods such as: "small group discussion, simulation, case study, discovery learning (DL), self-directed learning (SDL), cooperative learning (CL), project based learning (PJBL) and problem based learning an inquiry (PBL)" can be used.